Localized Method of Fundamental Solutions for Acoustic Analysis Inside a Car Cavity with Sound-Absorbing Material (Advances in Applied Mathematics and Mechanics, 2022)
This paper documents the first attempt to apply a localized method of fundamental solutions (LMFS) to the acoustic analysis of car cavity containing sound-absorbing materials. The LMFS is a recently developed meshless approach with themerits of being mathematically simple, numerically accurate, and requiring less computer time and storage. Compared with the traditional method of fundamental solutions (MFS) with a full interpolation matrix, the LMFS can obtain a sparse bandedlinear algebraic system, and can circumvent the perplexing issue of fictitious boundary encountered in the MFS for complex solution domains. In the LMFS, only circularor spherical fictitious boundary is involved. Based on these advantages, the methodcan be regarded as a competitive alternative to the standard method, especially forhigh-dimensional and large-scale problems. Three benchmark numerical examplesare provided to verify the effectiveness and performance of the present method for thesolution of car cavity acoustic problems with impedance conditions.